Film Serials and the American Cinema, 1910-1940 : Operational Detection - Brasch, Ilka (Book collections on Project MUSE., 2018)
Before the advent of television, cinema offered serialised films as a source of weekly entertainment. This book traces the history from the days of silent screen heroines to the sound era's daring adventure serials, unearthing a thriving film culture beyond the self-contained feature. Through extensive archival research, Ilka Brasch details the aesthetic appeals of film serials within their context of marketing and exhibition and that they adapt the pleasures of a flourishing crime fiction culture to both serialised visual culture and the affordances of the media-modernity of the early 20th century. The study furthermore traces how film serials brought the broadcast model of radio and television to the big screen and thereby introduced models of serial storytelling that informed popular culture even beyond the serial's demise.